Errors in the estimation of hydration status from changes in body mass - Maughan, R. J.; Shirreffs, S. M.; Leiper, J. B. (Journal of Sports Sciences, 2007)
Hydration status is not easily measured, but acute changes in hydration status are often estimated from body mass change. Changes in body mass are also often used as a proxy measure for sweat losses. There are, however, several sources of error that may give rise to misleading results, and our aim in this paper is to quantify these potential errors. Respiratory water losses can be substantial during hard work in dry environments. Mass loss also results from substrate oxidation, but this generates water of oxidation which is added to the body water pool, thus dissociating changes in body mass and hydration status: fat oxidation actually results in a net gain in body mass as the mass of carbon dioxide generated is less than the mass of oxygen consumed. Water stored with muscle glycogen is presumed to be made available as endogenous carbohydrate stores are oxidized. Fluid ingestion and sweat loss complicate the picture by altering body water distribution. Loss of hypotonic sweat results in increased osmolality of body fluids. Urine and faecal losses can be measured easily, but changes in the water content of the bladder and the gastrointestinal tract cannot. Body mass change is not always a reliable measure of changes in hydration status and substantial loss of mass may occur without an effective net negative fluid balance.